The Impact Of Variables Related to Letter of credits on The Problems Facing The Iraqi Importer - Applied Research in a sample of Private Banks - easj easj (مجلة الدراسات الاقتصادية والادارية)
This research aims to identify the problems facing the Iraqi importer when using letter of  credits and their degree, as well as identifying the effect of each of the following variables  (nationality of the bank issuing the letter of credit-capital of the customer who wants to open the letter of credit-the currency in which the importer will pay the value of the  letter of credit-type of ownership-The beneficiary of the letter of credit) related to letter of  credits in the problems facing the Iraqi importer. After conducting statistical analysis, it became clear that the degree of overall problems was high, and the most prominent of these problems was fluctuation in the currency exchange rate, It was also noted that there are statistically significant differences in the problems facing the Iraqi importer due to the variable of the nationality of the bank issuing the letter of credit and the variable of the capital of the customer who wishes to open the  letter of credit related to letter of credits, while there are no statistically significant differences for the remaining variables,  As for Its most important recommendations are the need to address the problem of exchange rate fluctuation through joint cooperation between the Central Bank of Iraq and banks by developing a mechanism for dealing with futures contracts so that the Iraqi importer can conduct what is called hedging, in addition to the need for the Central Bank of Iraq to allow banks to use what are called operations. Exchange and benefit from the experiences of neighboring countries, such as Jordan, for example.